Bioethical aspects of the relationship between professional of health and transplant patient - García Rodríguez, Keytel (Pensando Psicología, 2010)
The present article attempts an approach to the topic of the ethical aspects of the transplant of organs, being centered fundamentally in the relationship that settles down between the worker of the health and the patient or family of the same one. It is about a group of refl ections based on our professional chore, in the attention to the patients in waiting list and transplanted, their relatives as well as in the discussion cabinets, basing us on the basic principles of the bioethics and ethical dilemmas. As essential conclusion we think that the relationship sanitarium-patient team constitutes from its communication dimension a demanding source of professionalism, ethics and humanism, before the different dilemmas and ethical confl icts that show up.